Effectiveness of soil and water conservation structures in increasing community perception and controlling erosion and sedimentation. Issue 1 (October 2021) - Nugroho, H Y S H; Sallata, M K; Isnan, W; Saad, M; Hermawan, A
Abstract: The increasing frequency of floods and landslides has prompted the Ministry of Environment and Forestry to intensify the construction of soil and water conservation (SWC) structures in various watersheds in Indonesia. However, the evidence on how the high-cost measure can effectively increase community perception and participation while controlling erosion and sedimentation is still limited. For this reason, this preliminary research was conducted in 2019 to observe community perception and assess the effectiveness of the SWC structures in controlling gully erosion and sedimentation. The activities carried out in the Jeneberang and Lisu Sub Watershedsconsisted of two parts: 1) social and economic data collectionand 2) observing the effectiveness of the SWC structures in controlling sedimentation. Based on the socio-economic survey, respondents in the Jeneberang showed a better understanding and higher incomes than respondents in the Lisu Sub Watershed, despite their lowereducation levels.These phenomena relateto the length of time the community has learnedfrom surrounding examples and the applied SWC techniques on their land.In terms of the effectiveness of SWC structures, more than half of the retaining dam and gully plug capacityhad been filled with sediment in just oneyear after construction and is expected to be full at the end of the rainy season.The leadingcause is the high erosion of the tillage area on both sides.As a suggestion, agricultural land in the catchment area needs to be managed by applying SWC techniques according to site conditions through incentives given to landowners.